2005
DOI: 10.1039/b503589a
|View full text |Cite
|
Sign up to set email alerts
|

Exchange coupling in µ-aqua:µ-oxo vs. di-µ-hydroxo dinuclear Cu(ii) compounds: a density functional study

Abstract: Theoretical methods based on density functional theory have been applied to study the differences in exchange coupling between the di-mu-hydroxo and mu-aqua:mu-oxo tautomers of a dinuclear Cu(II) complex. The calculations indicate that the two compounds are totally different from a magnetic point of view. The transfer of one proton from one of the two hydroxo bridges to the other leaves an asymmetric structure with only one effective exchange pathway through the oxo bridge. The coordinated water molecule and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…[15,16,46,51] Chloride (Cl À ) and/ or hydroxide (OH À ) ions could be the bridging ligands in the copper complexes in materials 7 b and 7 c. [15,16] In the case of the material prepared with Cu II perchlorate precursor (7 a) a very weak absorption at half field was detected, indicating that the two copper ions are weakly coupled through the exogenous bridging ligands, such as water molecules. [52][53][54][55] When the EPR operating temperature was further lowered to 4 K (liquid helium temperature), the EPR signal remained broad and weakly resolved. However, the fact that the sample 7 a incorporating perchlorate (ClO 4 À ) showed two distinct g tensors indicated the dynamic nature of the dinuclear copper complexes grafted within the mesoporous channels.…”
mentioning
confidence: 99%
“…[15,16,46,51] Chloride (Cl À ) and/ or hydroxide (OH À ) ions could be the bridging ligands in the copper complexes in materials 7 b and 7 c. [15,16] In the case of the material prepared with Cu II perchlorate precursor (7 a) a very weak absorption at half field was detected, indicating that the two copper ions are weakly coupled through the exogenous bridging ligands, such as water molecules. [52][53][54][55] When the EPR operating temperature was further lowered to 4 K (liquid helium temperature), the EPR signal remained broad and weakly resolved. However, the fact that the sample 7 a incorporating perchlorate (ClO 4 À ) showed two distinct g tensors indicated the dynamic nature of the dinuclear copper complexes grafted within the mesoporous channels.…”
mentioning
confidence: 99%
“…For the ferromagnetic cation in the dinuclear compound 2 , the broken symmetry result for J is 42.2 cm –1 (without spin projection) which compares well with the experimental value of 36.9 cm –1 . It should be mentioned that different equations have been employed in the literature, for relating the energy gap between low spin (broken symmetry) and high spin states to the magnetic exchange parameter ( J ). It has been recently pointed out that the spin projected expression which corrects for spin contamination in the broken symmetry sate is preferable when advanced correlation functionals are employed in DFT, especially those with enhanced Fock exchange ,,.…”
Section: Resultsmentioning
confidence: 99%
“…33 These authors proposed that the antiferromagnetic coupling observed for the tautomer with the (m-OH) 2 bridge is turned into ferromagnetic coupling in the tautomer with the (m-OH 2 )(m-O) bridge, which implies that the transfer of one proton from one of the two hydroxo bridges to the other gives rise to an asymmetric structure with totally different magnetic properties. These experimental results were more recently theoretically analyzed and critiqued by Rodríguez-Fortea et al, 34 who suggest that the tautomer with the (m-OH 2 )(m-O) bridge is energetically unfavourable and that the unexpected magnetic behaviour could be produced by packing forces in the crystal lattice that distort the (m-OH) 2 bridge, leading to a ferromagnetic interaction. We cannot discard that this could also be occurring in the Cu(II) dinuclear compound studied here, since a free water molecule is within a hydrogen bond distance with the bridging hydroxo group and is also interacting via H bonds with the BF 4…”
Section: Magnetic Propertiesmentioning
confidence: 99%